2016
DOI: 10.3847/0004-637x/832/1/4
|View full text |Cite
|
Sign up to set email alerts
|

The Mid-Infrared Evolution of the Fu Orionis Disk

Abstract: We present new SOFIA-FORCAST observations obtained in 2016 February of the archetypal outbursting lowmassyoung stellar object FU Orionis, and wecompare the continuum, solid-state, and gas properties with midinfrareddata obtained at the same wavelengths in 2004 with Spitzer-IRS. In this study, we conduct the first midinfraredspectroscopic comparison of an FUor over a long time period. Over a 12-year period, UBVR monitoring indicates that FU Orionis has continued its steady decrease in overall brightness by … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…For a few au scale circumstellar disks, the characteristic variational time scale may be as short as a few years (e.g., dynamical timescale). On the other hand, there is not yet observational evidence for flux variability at >20 µm wavelengths (e.g., Green et al 2016). Finally, it is also possible that the JVLA, SMA, and ALMA observations have recovered all fluxes at the observed frequency bands without being affected by missing short spacing issues.…”
Section: Resultsmentioning
confidence: 99%
“…For a few au scale circumstellar disks, the characteristic variational time scale may be as short as a few years (e.g., dynamical timescale). On the other hand, there is not yet observational evidence for flux variability at >20 µm wavelengths (e.g., Green et al 2016). Finally, it is also possible that the JVLA, SMA, and ALMA observations have recovered all fluxes at the observed frequency bands without being affected by missing short spacing issues.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, we found that once a good fit for the interferometric data was achieved, the infrared spectrum predicted from the model is also very close to the Spitzer and Herschel observations. Green et al 2006Green et al , 2013Green et al , 2016a, and the fluxes of the au scales structures around FU Ori taken with the VLTI/GRAVITY (i.e., the "Extended" column of Table 4). Black lines show our model of the combined fluxes of these two sources.…”
Section: Abstracted Geometric Model and Integrated Sedsmentioning
confidence: 99%
“…The second form appeals to the century scale (Hartmann & Kenyon 1996;Green et al 2016) heating from an FU Orionis scale accretion event, which would provide the required heating for the required time out to an orbital location between Venus' orbit and Mars'. The heating time scale and resulting radial planetesimal distribution would be consistent with Earth's composition (Hubbard & Ebel 2014) and with Mars' small size (Chambers 2014); and appeals to a process that we have proposed to promote the formation of Jupiter and Saturn-like gas giants (Hubbard 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Hubbard & Ebel (2014) put forth a model to explain the Earth's abundance pattern through timedependent heating and cooling from an FU Orionis type event in the early Solar System (Hartmann & Kenyon 1996). FU Orionis type events are dramatic, long lived accretion events, associated with luminosity increases of 4 − 6 magnitudes and time scales of 50 − 100 yr (Hartmann & Kenyon 1996;Green et al 2016). FU Orionis events (or FUors) can raise the temperature at Earth's orbital position to about 1350 K (Hubbard & Ebel 2014), and drive the frost line out to about 40 au (Cieza et al 2016).…”
Section: Fu Orionis Type Eventsmentioning
confidence: 99%